Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together terhadap Keterampilan Passing Kaki Bagian Dalam Sepak Bola Pada Siswa SMP Islam Karawang - Ahmad Fikri; Suprananto; Rolly Afrinaldi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the cooperative learning model Numbered Heads Together (NHT) on the basic inside-foot passing skills in soccer among eighth-grade students at SMP Islam Karawang. The research method employed was an experimental approach using a one-group pretest-posttest design. The sample consisted of 26 eighth-grade students selected through saturated sampling. The research instrument was a passing skill test based on standard soccer assessment criteria. The results of the Wilcoxon Signed Ranks Test analysis showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. A total of 23 students showed improvement in their skills, 1 student showed a decline, and 2 students remained unchanged. These findings demonstrate that the implementation of the NHT model has a significant effect on improving inside-foot passing skills. Therefore, the NHT model can be recommended as an alternative instructional strategy in physical education.